Endogenous microparticles drive the proinflammatory host immune response in severely injured trauma patients - Balvers, Kirsten; Curry, Nicola; Kleinveld, Derek J B; Böing, Anita N; Nieuwland, Rienk; Goslings, J Carel; Juffermans, Nicole P (Shock (Augusta, Ga.), 2015)
Severe trauma affects the immune system, which in its turn is associated with poor outcome. The mediators driving the immune responses in trauma are largely unknown. The aim of this study was to investigate the role of endogenous microparticles (MPs) in mediating the immune response following severe trauma. A prospective, observational substudy of the ACIT II (Activation of Coagulation and Inflammation in Trauma II) study was performed at our academic level I trauma center. Adult multiple-trauma patients with an injury severity score of 15 or higher were included between May 2012 and June 2013. Ex vivo whole-blood stimulation with lipopolysaccharide was performed on aseptically collected patient plasma containing MPs and in plasma depleted of MPs. Flow cytometry and transmission electronic microscopy were performed on plasma samples to investigate the numbers and cellular origin of MPs. Healthy individuals served as a control group. Ten trauma patients and 10 control subjects were included. Trauma patients were significantly injured with a median injury severity score of 19 (range, 17-45). Patients were neither in shock nor bleeding. On admission to the hospital, the host response to bacterial stimulation was blunted in trauma patients compared with control subjects, as reflected by decreased production of interleukin 6 (IL-6), IL-10, and tumor necrosis factor α (P < 0.001). In trauma patients, MP-positive plasma was associated with a significantly higher synthesis of IL-6 and tumor necrosis factor α compared with plasma depleted from MPs (P = 0.047 and 0.002, respectively). Compared with control subjects, the number of circulating MPs was significantly decreased in trauma patients (P = 0.009). Most MPs originated from platelets. Multiple cellular protrusions, which result in MP formation, were observed in plasma from trauma patients, but not in control subjects. On admission, trauma patients have a reduced immune response toward endotoxin challenge, which is, at least in part, mediated by MPs, which circulate in low numbers and in early stages. Most MPs originate from platelets, which indicates that these cells may be the most important source of MPs involved in initiating an inflammatory host response after injury.